Particle‐resolved simulations of methane steam reforming in multilayered packed beds - G. M., Karthik; Buwa, Vivek V. (AIChE journal, 2018)
Particle‐resolved CFD simulations of multilayered packed beds containing 30 particles of different particle shapes (trilobe, daisy, hollow cylinder, cylcut, and 7‐hole cylinder) with a tube to particle diameter ratio of 5, were performed to understand the effect of particle shape on pressure drop (ΔP), dispersion, CH4 conversion and effectiveness factors for methane steam reforming reactions. The effect of different boundary conditions and particle modeling approaches were analyzed in detail. The empirical correlations (Ergun and Zhavoronkov et al.) over‐predicted the ΔP and a modified correlation was developed to predict ΔP for the particles with different shapes. Overall, the externally shaped particles (trilobe and daisy) offered lower ΔP and higher dispersion because of the lower surface area and higher back flow regions, whereas the internally shaped particles (cylcut, hollow, and 7‐hole cylinder) offered higher CH4 conversion and effectiveness factors because of the better access for the reactants. The cylcut‐shape offered the highest CH4 conversion/ΔP. © 2018 American Institute of Chemical Engineers AIChE J, 64: 4162–4176, 2018